Mortal kombat legends, Cage match [videorecording (Blu-Ray)] - Adams, Jeremy (Screenwriter) (Warner Bros., 2023)
Johnny Cage, the world's number one action superstar, is having a rotten day. After a young starlet was kidnapped from his latest blockbuster, Johnny is pulled into a mystery that will lead him through 1980s Los Angeles, from Grauman's to the Hollywood sign, and into the seedy underbelly, where he'll find a dark and sinister secret that might have lasting effects on the city...and more importantly, Johnny's career!